2011
DOI: 10.1016/j.jpsychires.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders associated with full and partial posttraumatic stress disorder in the U.S. population: Results from Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Background While it is well known that personality disorders are associated with trauma exposure and PTSD, limited nationally representative data are available on DSM-IV personality disorders that co-occur with posttraumatic stress disorder (PTSD) and partial PTSD. Methods Face-to-face interviews were conducted with 34,653 adults participating in the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions. Logistic regression analyses controlling for sociodemographics and additional psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 106 publications
3
39
1
4
Order By: Relevance
“…A connection between PTSD and the axis II disorders avoidant (Ansell et al, 2011), obsessive-compulsive (Pietrzak et al, 2011) and borderline PDs have been established (Bienvenu and Stein, 2003b;Pagura et al, 2010;Shea et al, 1999), but also with paranoid and schizotypal PDs (Crepulja and Franciskovic, 2010;Pietrzak et al, 2011). Paranoid traits are understandable as PTSD patients often feel a constant need to be vigilant and on guard.…”
Section: Associated Dysfunctions With Pd and Expected Rates Of Comorbmentioning
confidence: 99%
“…A connection between PTSD and the axis II disorders avoidant (Ansell et al, 2011), obsessive-compulsive (Pietrzak et al, 2011) and borderline PDs have been established (Bienvenu and Stein, 2003b;Pagura et al, 2010;Shea et al, 1999), but also with paranoid and schizotypal PDs (Crepulja and Franciskovic, 2010;Pietrzak et al, 2011). Paranoid traits are understandable as PTSD patients often feel a constant need to be vigilant and on guard.…”
Section: Associated Dysfunctions With Pd and Expected Rates Of Comorbmentioning
confidence: 99%
“…With regard to studies in community samples, some of the main research in the general adult population showed that the prevalence of PTSD ranges from 3 to 6% [4,5,6]. Specifically, when data are from subjects diagnosed with BPD, the range of people with PTSD increases to 30-70% [7,8,9].…”
Section: Prevalence Of Comorbidity Between Ptsd and Bpdmentioning
confidence: 99%
“…Specifically, when data are from subjects diagnosed with BPD, the range of people with PTSD increases to 30-70% [7,8,9]. Likewise, results from subjects with a primary diagnosis of PTSD also point out that BPD comorbidity is estimated to occur in 22-24% [6,7]. Despite this high comorbidity, different comparative studies have found no conclusive evidence about a higher relative prevalence of PTSD in subjects diagnosed with BPD than in people with other personality disorders [6,10]…”
Section: Prevalence Of Comorbidity Between Ptsd and Bpdmentioning
confidence: 99%
“…For example, in the NCS, Kessler, Sonnega, et al (1995) found that PTSD was associated with an increased odds of being diagnosed with a mood disorder, an anxiety disorder, alcohol/drug abuse or dependence, and conduct disorders. The mood disorder most commonly comorbid with PTSD is consistently found to be major depressive disorder (MDD; Brown et al, 2001;Pietrzak, Goldstein, Southwick, & Grant, 2011). The most common comorbid anxiety disorder tends to vary by sample, ranging from generalized anxiety disorder (e.g., Brown et al, 2001) to specific phobia (e.g., Pietrzak et al, 2011).…”
Section: Comorbiditymentioning
confidence: 99%
“…The mood disorder most commonly comorbid with PTSD is consistently found to be major depressive disorder (MDD; Brown et al, 2001;Pietrzak, Goldstein, Southwick, & Grant, 2011). The most common comorbid anxiety disorder tends to vary by sample, ranging from generalized anxiety disorder (e.g., Brown et al, 2001) to specific phobia (e.g., Pietrzak et al, 2011). Alcohol and drug abuse and dependence are consistently found to be highly comorbid with PTSD as well (Brown et al, 2001;Pietrzak et al, 2011).…”
Section: Comorbiditymentioning
confidence: 99%